2011
DOI: 10.1016/j.crci.2011.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Squaric acid as an impressive organocatalyst for Michael addition in water

Abstract: A simple, green, and environmentally benign protocol for squaric acid (5 mg) catalyst conjugate addition of aromatic amines and thiols to unsaturated carbonyl compounds in water in good to excellent yields is developed. The advantages of low sensitivity toward moisture and oxygen, high tolerance of different functional groups, green reaction media and efficient recyclability make this organocatalyst suitable for both laboratory and industrial scale synthesis of b-substituted carbonyls under very mild condition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 62 publications
0
10
0
Order By: Relevance
“…The 1,4-conjugate addition of primary and secondary aniline derivative to various Michael acceptor motifs has been widely reported [ [43] , [44] , [45] , [46] , [47] , [48] , [49] ], including related natural product derived lactones [ 38 , 41 , 43 , 44 , 50 ] that have been shown to be amenable to Lewis or Brønsted acid catalysed conjugate addition of anilines. In order to extend the scope of such aniline derivative additions to parthenolide ( 1 ) a series of model, precedent-informed, reactions were investigated.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The 1,4-conjugate addition of primary and secondary aniline derivative to various Michael acceptor motifs has been widely reported [ [43] , [44] , [45] , [46] , [47] , [48] , [49] ], including related natural product derived lactones [ 38 , 41 , 43 , 44 , 50 ] that have been shown to be amenable to Lewis or Brønsted acid catalysed conjugate addition of anilines. In order to extend the scope of such aniline derivative additions to parthenolide ( 1 ) a series of model, precedent-informed, reactions were investigated.…”
Section: Resultsmentioning
confidence: 99%
“…Azizi et al . showed that squaric acid was an excellent organocatalyst for the addition of aromatic amines (and thiols) to Michael acceptors under aqueous conditions [ 46 ]. The formation of 6 under control of squaric acid as catalyst (10 mol%) in water at room temperature proceeded in 39% yield ( Table 1 , entry 12).…”
Section: Resultsmentioning
confidence: 99%
“…[34][35] The oxocarbon acids are very relevant materials in organic reactivity studies. 36 The good results obtained for the structural properties of these materials in the previous work 6 encouraged the determination of their mechanical properties. These acids in the solid state were shown to display negative Poisson ratios (NPR).…”
Section: Introductionmentioning
confidence: 88%
“…Due to our interest in developing new green media for organic syntheses [21][22][23][24][25], herein we describe a onepot, three-component passerini reaction in DES as a green solvent and catalyst for -acyloxycarboxamides synthesis. Furthermore, the isolation and puri cation steps of this DES are very simple and easy.…”
Section: Resultsmentioning
confidence: 99%